AB thymoma with atypical type A component with delayed multiple lung and brain metastases - Grajkowska, Wiesława; Marx, Alexander; Weis, Cleo-Aron Thias (Journal of thoracic disease, 2017)
An atypical type A thymoma is a newly added entity to the last World Health Organization (WHO) histological classification [2015] of uncertain prognosis. The conventional type A and AB thymomas are usually locally aggressive neoplasms that rarely metastasize with distant metastases to the central nervous system (CNS) occurring extremely exceptionally. We present a history of a woman with a mediastinal tumor originally considered to be a Masaoka-Koga stage II “mixed thymoma with well-differentiated thymic carcinoma component” according to the historic Müller-Hermelink nomenclature. By applying the criteria of the new WHO classification the tumor should be reclassified as an AB thymoma with an atypical A component. The patient developed metastases to the lung and brain 10 and 15 years after the original diagnosis, respectively. All metastases morphologically corresponded to an atypical A component of primary thymoma. Molecular study revealed GTF2I mutations in the primary and one of the metastatic tumors. To our knowledge, this is the first description of a GTF2I mutation in AB thymoma with atypical A component and its metastases. The presented case highlights the necessity of an accurate microscopic search for atypical areas in A or AB thymomas because of their potentially negative impact on prognosis.